Occurrence of blood-borne tick-transmitted parasites in tsessebe (Damaliscus lunatus lunatus) antelope in Vaalbos National Park, Northern Cape Province - Penzhorn, Barend Louis (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.